FIFO Method for Optimizing Pharmaceutical Inventory Management at the Pharmaceutical Installation Unit of the Pekalongan District Health Office: Metode FIFO Untuk Optimasi Pengelolaan Persediaan Obat Di Upt Instalasi Farmasi Dinas Kesehatan Kabupaten Pekalongan - Mohamad Irsyad Mutaqin; Dewi Handayani Untari Ningsih (JOINCS (Journal of Informatics, Network, and Computer Science), 2026)
Abstract. Effective drug inventory management is crucial for ensuring drug availability and ensuring smooth healthcare services. The Pekalongan District Health Office's Pharmacy Installation Unit (UPT) still faces challenges in inventory management due to the use of a semi-computerized Microsoft Excel-based system that can potentially lead to recording errors, difficulty monitoring stock, and delays in reporting. Based on drug inventory data from January to December 2025, the number of incoming drugs was 10,964,906 and outgoing drugs was 20,460,686, with a difference of 9,495,780 and a distribution ratio of 186.6%, indicating an imbalance between drug receipts and expenditures and potential pressure on stock availability. This study aims to optimize drug inventory management through the application of the First In First Out (FIFO) method, a method that prioritizes drug expenditure based on the order of receipt. The research method used is descriptive with analysis of available drug inventory data. The results show that the application of the FIFO method can improve orderly stock management, minimize the risk of expiration, and improve the accuracy of recording and reporting. Thus, the FIFO method can be an effective solution in improving the efficiency and effectiveness of drug inventory management. Keywords: FIFO, Drug Inventory, Inventory Management, Pharmaceutical Installation, Optimization. Abstrak. Pengelolaan persediaan obat yang efektif sangat penting dalam menjamin ketersediaan obat dan kelancaran pelayanan kesehatan. UPT Instalasi Farmasi Dinas Kesehatan Kabupaten Pekalongan masih menghadapi kendala dalam pengelolaan persediaan karena penggunaan sistem semi komputerisasi berbasis Microsoft Excel yang berpotensi menimbulkan kesalahan pencatatan, kesulitan monitoring stok, dan keterlambatan pelaporan. Berdasarkan data persediaan obat periode Januari hingga Desember 2025, jumlah obat masuk sebesar 10.964.906 dan obat keluar sebesar 20.460.686, dengan selisih 9.495.780 serta rasio distribusi mencapai 186,6%, yang menunjukkan ketidakseimbangan antara penerimaan dan pengeluaran obat serta potensi tekanan terhadap ketersediaan stok. Penelitian ini bertujuan mengoptimalkan pengelolaan persediaan obat melalui penerapan metode First In First Out (FIFO), yaitu metode yang mengutamakan pengeluaran obat berdasarkan urutan waktu masuk. Metode penelitian yang digunakan adalah deskriptif dengan analisis terhadap data persediaan obat yang tersedia. Hasil penelitian menunjukkan bahwa penerapan metode FIFO mampu meningkatkan ketertiban pengelolaan stok, meminimalkan risiko kadaluarsa, serta meningkatkan akurasi pencatatan dan pelaporan. Dengan demikian, metode FIFO dapat menjadi solusi yang efektif dalam meningkatkan efisiensi dan efektivitas pengelolaan persediaan obat. Kata Kunci: FIFO, Persediaan Obat, Manajemen Persediaan, Instalasi Farmasi, Optimasi